Portuguese war veterans: Moral injury and factors related to recovery from PTSD - Ferrajão, Paulo (2017)
This study explored the factors to which a sample of Portuguese war veterans attributed their recovery from posttraumatic stress disorder (PTSD). Participants were a sample of veterans (N = 60) with mental sequelae of the Portuguese Colonial War: 30 suffered from chronic PTSD (unrecovered) and 30 veterans with remission from PTSD (recovered). Two semistructured interviews were conducted. Analysis of the interviews was conducted using the Thematic and Categorical Analysis. Results showed that unrecovered participants reported higher postwar betrayal, appraisal of hostile societal homecoming, social stigmatization, lack of personal resources (mental fatigue and restriction of coping strategies), and reduced perceived social support. Recovered participants verbalized some capability for self-awareness of their own mental states and/or awareness of others' mental states (mentalization ability), a wider repertoire of coping strategies, and higher perceived social support. The authors discussed that recovery from PTSD among veterans can be related to the assimilation of moral injury by developing higher mentalization abilities.